2017
DOI: 10.11648/j.sjph.20170502.14
|View full text |Cite
|
Sign up to set email alerts
|

Bypassing Primary Health Care Facilities for Common Childhood Illnesses in Sharg-Alneel Locality in Khartoum State, Sudan 2015

Abstract: Abstract:In Sudan despite the current implementation of universal health coverage policy, routine monitoring reports highlight that patients frequently bypass Primary Health Care (PHC) facilities in favor of higher-level hospitals, though hospitals are costly and time consuming. The main objective of this study was to study the extent of bypassing the public PHC facilities and factors associated with the decision of caretakers to bypass such facilities seeking care for their under-five year's children with com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
1
2
1
Order By: Relevance
“…These results were in keeping with other studies conducted in Sharg-Alneel Locality in Khartoum State Sudan by Ahmed, et al (2015) found primary healthcare facility bypass was very high at 87% of them pursued healthcare for their children directly from secondary hospitals [13]. Kante, et al, (2016) on the other side also established that more than 75.4% bypassed the primary facilities in rural Tanzania which is lower than this study has established [8].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results were in keeping with other studies conducted in Sharg-Alneel Locality in Khartoum State Sudan by Ahmed, et al (2015) found primary healthcare facility bypass was very high at 87% of them pursued healthcare for their children directly from secondary hospitals [13]. Kante, et al, (2016) on the other side also established that more than 75.4% bypassed the primary facilities in rural Tanzania which is lower than this study has established [8].…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, in Ghana Yafee, et al [12] established that, 33.9% was the total rate of bypassing a local facility and in Sudan, Ahmed, et al [13] found that primary health facility bypass was very high at 87%…”
Section: Summary Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The finding of this study was lower as compared with studies conducted in DCSH, Ethiopia (63.9%) ( 25 ), Western Ethiopia (82 and 84%) ( 4 , 35 ), Indonesia (66%) ( 10 ), Nigeria (70%) ( 12 ), and Sudan (87%) ( 11 ) of outpatients who were self-referred. This difference might be due to a difference in the study population, which means labor is acute and progressive; women may not be able to walk as far as outpatients.…”
Section: Discussioncontrasting
confidence: 85%